HbA1c control in type 2 diabetes mellitus patients with coronary artery disease: a retrospective study in a tertiary hospital in South Africa - Mhlaba, Lona; Mpanya, Dineo; Tsabedze, Nqoba (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Type 2 diabetes mellitus (T2DM) patients with coronary artery disease (CAD) have an increased risk of recurrent cardiovascular events. These patients require optimal glucose control to prevent the progression of atherosclerotic cardiovascular disease (ASCVD). Contemporary guidelines recommend an HbA1c ≤7% to mitigate this risk. The aim of this study was to evaluate HbA1c control in T2DM patients with angiographically proven ASCVD. Methods We conducted a cross-sectional, retrospective study on consecutive T2DM patients with acute and chronic coronary syndromes managed in a tertiary academic hospital in South Africa. Glycaemic control was assessed by evaluating the glycated haemoglobin (HbA1c) level measured at index presentation with acute and chronic coronary syndromes and during the most recent follow-up visit. Results The study population comprised 262 T2DM patients with a mean age of 61.3 ± 10.4 years. At index presentation, 110 (42.0%) T2DM patients presented with ST-segment elevation myocardial infarction, 69 (26.3%) had non-ST-segment elevation myocardial infarction, 43 (16.4%) had unstable angina, and 40 (15.3%) had stable angina. After a median duration of 16.5 months (IQR: 7-29), 28.7% of the study participants had an HbA1c ≤7%. On multivariable logistic regression analysis, females were less likely to have poor glycaemic control (HbA1c above 7%) [odds ratio (OR): 0.42, 95% confidence interval (CI): 0.19-0.95, p=0.038]. Also, T2DM patients prescribed metformin monotherapy (OR: 0.34, 95% CI: 0.14-0.82, p=0.017) and patients with ST-segment depression on the electrocardiogram (OR: 0.39, 95% CI: 0.16-0.96, p=0.041) were less likely to have poor glycaemic control. Conclusion After a median duration of 16.5 months, only 28.7% of T2DM patients with CAD had an HbA1c ≤7%. This finding underscores the substantial unmet need for optimal diabetes control in this very high-risk group.